FGF/FGFR signaling: From lung development to respiratory diseases. (December 2021) - Yang, Lehe; Zhou, Feng; Zheng, Dandan; Wang, Dandan; Li, Xiaokun; Zhao, Chengguang; Huang, Xiaoying
Abstract: The fibroblast growth factor/fibroblast growth factor receptor (FGF/FGFR) signaling system regulates a variety of biological processes, including embryogenesis, angiogenesis, wound repair, tissue homeostasis, and cancer. It exerts these regulatory functions by controlling proliferation, differentiation, migration, survival, and metabolism of target cells. The morphological structure of the lung is a complex tree-like network for effective oxygen exchange, and the airway terminates in the middle and distal ends of many alveoli. FGF/FGFR signaling plays an important role in the pathophysiology of lung development and pathogenesis of various human respiratory diseases. Here, we mainly review recent advances in FGF/FGFR signaling during human lung development and respiratory diseases, including lung cancer, acute lung injury (ALI), pulmonary arterial hypertension (PAH), chronic obstructive pulmonary disease (COPD), asthma, and pulmonary fibrosis. Graphical Abstract: ga1 Highlights: The role of FGF/FGFR signaling in human lung development and respiratory disease remains poorly understood. Many studies have shown the importance of FGF/FGFR signaling in the development of lung and in various respiratory diseases. Understanding the role of FGF/FGFR signaling will help tailor its effects and targets to action sites and patients.